CHANGES IN LIVE WEIGHT AND GROWTH RATE OF REPAIR HEIFERS DUE TO THE USE OF DIFFERENT SILAGES IN THEIR RATIONS - Drozdova, Oksana (SWorld-Ger Conference proceedings, 2023)
The article experimentally substantiates the dynamics of changes in live weight and growth intensity of repair heifers of the Ukrainian Black-and-White dairy breed using silage from a mixture of corn and sorghum. The replacement of silage in the rations o